1996
DOI: 10.2514/3.24095
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal mixing in coaxial supersonic jets

Abstract: An experimental study was conducted to investigate the thermal mixing of a hot, supersonic, primary jet of combustion gases with a coflowing secondary jet of air at ambient temperature. The Mach numbers of the two jets were 1.2 and 1.7, respectively. To enhance the mixing, the core (primary) jet was admitted through a three-dimensional, radially lobed nozzle, referred to as the petal nozzle. The uniformity of stagnation temperature in the flowfield was used to characterize the extent of mixing between the jets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…A similar approach has been followed in several previous studies on mixing enhancement (e.g. [7,9,10]).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar approach has been followed in several previous studies on mixing enhancement (e.g. [7,9,10]).…”
Section: Introductionmentioning
confidence: 97%
“…The triangular tab was found to be a better mixing promoter compared with the rectangular tab. Srikrishnan et al [9,10] have reported mixing enhancement studies using lobed nozzles in co-flowing supersonic jet streams. Nastase et al [11], Nastase and Meslem [12,13] and El Hassan and Meslem [14] carried out comprehensive flow visualization and PIV measurements on cross-orifice jets, daisy-shaped orifice jets and lobed jets.…”
Section: Introductionmentioning
confidence: 99%